S+15=-9

Solution:
Simplifying
s + 15 = -9

Reorder the terms:
15 + s = -9

Solving
15 + s = -9

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-15' to each side of the equation.
15 + -15 + s = -9 + -15

Combine like terms: 15 + -15 = 0
0 + s = -9 + -15
s = -9 + -15

Combine like terms: -9 + -15 = -24
s = -24

Simplifying
s = -24

1

Answers

2016-07-20T20:40:30+08:00
   s + 15 =  -9
   s  =  - 9 -15    /  just reverse the sign
   s  = -24
0